1992
DOI: 10.1002/mrm.1910250216
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of brain perfusion by volume‐localized NMR spectroscopy using inversion of arterial water spins: Accounting for transit time and cross‐relaxation

Abstract: The theoretical model for perfusion measurement by NMR using arterial labeling of endogenous water is extended to include the effects of transit time and cross-relaxation of tissue water with macromolecules. Water magnetization in rat brain is monitored using the STEAM method to simultaneously determine the transit time, magnetization transfer rate constant, and perfusion. The results show that the transit time in rat brain is quite short, and thus its effect on perfusion measurement is small. It is also demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 14 publications
7
117
0
3
Order By: Relevance
“…In a study by Sicard et al (31), administration of 5% CO 2 to spontaneously breathing, isoflurane-anesthetized animals resulted in a 25% increase of CBF with an average pCO 2 of 50 mm/Hg. A more pronounced increase in CBF was found in other studies with isoflurane (15), halothane (37,38), and ␣-chloralose (12). With a mean pCO 2 of 54.1 mm/Hg, our data are consistent with a 5% CBF change per mmHg CO 2 increase with invasive methods (39).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a study by Sicard et al (31), administration of 5% CO 2 to spontaneously breathing, isoflurane-anesthetized animals resulted in a 25% increase of CBF with an average pCO 2 of 50 mm/Hg. A more pronounced increase in CBF was found in other studies with isoflurane (15), halothane (37,38), and ␣-chloralose (12). With a mean pCO 2 of 54.1 mm/Hg, our data are consistent with a 5% CBF change per mmHg CO 2 increase with invasive methods (39).…”
Section: Discussionsupporting
confidence: 90%
“…Mean dt values decreased by 39%. Previous studies have reported tran-sit delay decreases by 13% with a pCO 2 of 70 mmHg in tissue voxels (15), and 48% with a pCO 2 of 86 mmHg (37). In a study by Sicard et al (31), administration of 5% CO 2 to spontaneously breathing, isoflurane-anesthetized animals resulted in a 25% increase of CBF with an average pCO 2 of 50 mm/Hg.…”
Section: Discussionmentioning
confidence: 91%
“…of the AST pulse and before imaging (19,23). This time interval allows delivery of the tagged blood spins to tissue voxels in the imaging slice and also enables washout of the tagged blood from the proximal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…When a single labeling/imaging RF coil is used, the off-resonance RF pulse required for ASL saturates macromolecules in the brain, resulting in a large spatially dependent decrease of the signal intensity due to magnetization transfer (MT) effects (38). The original way to account for MT effects was to acquire a control image with RF power applied on a plane symmetrically opposed to the labeling plane (37,38), which limited data acquisition to a single slice centered between the labeling and control planes.…”
Section: Use Of a Separate Labeling Rf Coilmentioning
confidence: 99%
“…When a single labeling/imaging RF coil is used, the off-resonance RF pulse required for ASL saturates macromolecules in the brain, resulting in a large spatially dependent decrease of the signal intensity due to magnetization transfer (MT) effects (38). The original way to account for MT effects was to acquire a control image with RF power applied on a plane symmetrically opposed to the labeling plane (37,38), which limited data acquisition to a single slice centered between the labeling and control planes. While some methods were proposed to extend the coverage of both PASL and CASL to multiple slices (39)(40)(41), MT effects still imposed a few hard to overcome constraints, such as imaging slice orientation restricted to the labeling direction (39,40) and reduction of the effective degree of spin labeling (41).…”
Section: Use Of a Separate Labeling Rf Coilmentioning
confidence: 99%